Short-term effect of sacubitril/valsartan on endothelial dysfunction and arterial stiffness in patients with chronic heart failure - Cassano, Velia; Armentaro, Giuseppe; Magurno, Marcello; Aiello, Vincenzo; Borrello, Francesco; Miceli, Sofia; Maio, Raffaele; Perticone, Maria; Marra, Alberto M.; Cittadini, Antonio; Hribal, Marta L.; Andreozzi, Francesco; et al. (Frontiers in Pharmacology, 2022)
Heart failure (HF) is associated to endothelial dysfunction that promotes the increase of arterial stiffness thus augmenting myocardial damage. Sacubitril/Valsartan is used in the treatment of HF reduced ejection fraction (HFrEF) and has been proven effective in reducing cardiovascular disease (CVD) progression and all-cause mortality. The aim of this study was to evaluate the effect of Sacubitril/Valsartan on endothelial dysfunction, arterial stiffness, oxidative stress levels and platelets activation in patients with HFrEF, at baseline and after 6 months of treatment. We enrolled 100 Caucasian patients. Endothelial function was evaluated by the reactive hyperemia index (RHI) and arterial stiffness (AS) by the measurement of carotid-femoral pulse wave velocity (PWV), augmentation pressure (AP) and augmentation index (AI). At baseline, among enrolled outpatients, 43% showed a NYHA class II and 57% a NYHA class III. At 6 months, there was a significant improvement of several hemodynamic, clinical and metabolic parameters with a significant reduction in oxidative stress indices such as 8-isoprostane (p < 0.0001) and Nox-2 (p < 0.0001), platelets activity biomarkers such as sP-selectin (p < 0.0001) and Glycoprotein-VI (p < 0.0001), and inflammatory indices. Moreover, we observed a significant improvement in arterial stiffness parameters and in endothelial function indices. Our study demonstrated that 6 months treatment with Sacubitril/Valsartan, in patients with HFrEF, improves endothelial dysfunction and arterial stiffness, by reducing oxidative stress, platelet activation and inflammation circulating biomarkers, without adverse effects.